Enhancing Healthcare Sustainability: Informal Caregivers Leveraging Social Media in the Caregiving Process - Dalia Yahia M. El Kheir; Raghad Y. Sonbul; Zahra N. Alqarrashi; Ethar M. Sewakat; Nersyan T. Sharbini (The Saudi Journal of Health Systems Research)
Introduction: Informal caregivers who offer unpaid assistance to family and friends in need navigate complex challenges during their caregiving journey. Seeking support and guidance, many caregivers turn to social media (SM) platforms, marking a crucial intersection between technology transfer, digital transformation, and sustainability in caregiving. Methods: Twenty-four caregivers from diverse regions of Saudi Arabia were interviewed, semi-structured interviews, to gauge the extent to which they utilized SM in caregiving tasks. Results: Our analysis revealed broad patterns of SM utilization among caregivers, characterized by four main themes. Most participants actively used SM platforms to seek medical information, communicate with physicians, and participate in support groups. Educational background influenced adoption patterns, with varying levels of engagement across educational attainment. While the majority leveraged multiple platforms, such as WhatsApp, Twitter, and Instagram, for medical information access and healthcare providers (HCPs) communication, some participants expressed reservations and hesitancy about SM use in caregiving. Notably, participants utilized these platforms for resource management and accessing educational materials about caregiving techniques, demonstrating the multifaceted role of SM in supporting informal caregivers. Conclusion: Our findings revealed widespread SM use among informal caregivers, depicting the adoption of new technologies and a shift toward secure, high-quality care. The caregivers leveraged SM for medical information, consultations, and support group participation. Nevertheless, skepticism exists with some caregivers not trusting SM as an enabler of caregiving duties. Future research may focus on enhancing caregivers’ experiences, facilitating their tasks, and improving their loved one’s health through wider technological deployment and digital health transformation activities.